Liquidity Position of PT Bina Karya Jaya Abadi Tbk in Three Periods - Lau, Elfreda Aplonia (PT. Riset Press International, 2023)
This study aims to determine and analyze the ability of PT Binakarya Jaya Abadi Tbk in fulfilling short-term obligations in three periods, namely the pre-pandemic, pandemic and after pandemic periods. The results showed that the liquidity position of PT Binakarya Jaya Abadi Tbk during the pandemic period, namely 2017, 2018 and 2019 was in a liquid state, as evidenced by the Current ratio above 200%. During the pandemic (2020 and 2021), PT Binakarya jaya Abadi Tbk’ s liquidity position was below 200%, namely in 2020 Current Ratio 117.860% and in 2021 Current ratio of 119.739%. Likewise after pandemic ,namely in 2022 the Liquidity of PT Bina karya Jaya Abadi Tbk was still below 200% even though it was better than the pandemic position. Furthermore, when measured by the Quick ratio and Cash ratio, the Liquidity position of PT. Binakarya jaya Abadi Tbk before the pandemic was below 100% and continued to decline during pandemic. Likewise during the post-pandemic period the liquidity position of PT. Binkarya jaya Abadi Tbk is in The Illiquid category. The results of this study also show that PT. Binakarya Jaya Abadi Tbk is also affected by the Corona Virus Disease 2019.